Construction of an ontology-based nursing knowledge system - Han Shi-Fan; Zhu Rui-Fang; Xue Jia; Yu Qi; Su Yan-Bing; Wang Xiu-Juan (Sciendo, 2018)
This study proposes the establishment of a knowledge-system ontology in the nursing field. It uses advanced data mining techniques, digital publishing technologies, and new media concepts to comprehensively integrate and deepen nursing knowledge and to aggregate sources of knowledge in specialized technical fields. This study applies all forms of media and transmission channels, such as personal computers and mobile devices, to establish a knowledge-transmission system that provides knowledge services such as knowledge search, update retrieval, evaluation, questions and answers (Q&As), online viewing, information subscription, expert services, push notifications, review forums, and online learning. In doing so, this study creates an authoritative and foundational knowledge service engine for the nursing field, which provides convenient, flexible, and comprehensive knowledge services to members of the nursing industry in a digital format.